Repetitions - Abbott, Scott H.; Radaković, Žarko (Book collections on Project MUSE., 2020)
In 1994, after following a character in Peter Handke's novel Repetition into what is now Slovenia and after traveling in landscapes of Handke's youth, Zarko Radakovic and Scott Abbott published a two-headed text in Belgrade, Ponavljane (Repetitions). The possibility of narration in two voices, complicated by the third voice that is Peter Handke's own narrator, is the main focus of deliberation while traveling and reading and writing. Repetitions begins with Abbott's text, a fairly straightforward travel narrative. It ends with Radakovic's account of the same events, much less straightforward, more repetitious, more adventuresome.First, the book is written by two authors whose native languages are Serbian and English respectively (German is their only common language). The authors' perspectives contrast with and supplement one another: Radakovic grew up in Tito's Yugoslavia and Abbott comes from the Mormon American West; Radakovic is the translator of most of Peter Handke's works into Serbo-Croatian and Abbott translated Handke's provocative A Journey to the Rivers: Justice for Serbia for Viking Press and his play Voyage by Dugout: The Play of the Film of the War for PAJ (Performing Arts Journal); Radakovic was a journalist for Deutsche Welle in Cologne and Abbott is a professor of German literature at Utah Valley University; Radakovic is the author of several novels and Abbott has published mostly literary-critical work; Radakovic was married to a theoretical physicist from Belgrade and Abbott was married to a homemaker with whom he had seven children; and so on. Two sets of eyes. Two pens. Two visions of the world.